Alleviating acute alcoholic liver injury in mice with Bacillus subtilis co-expressing alcohol dehydrogenase and acetaldehyde dehydrogenase. (October 2018) - Lu, Jing; Lyu, Yunbin; Li, Mingtong; Sun, Jing; Huang, Zhenghua; Lu, Fengxia; Lu, Zhaoxin
Graphical abstract: Highlights: B. subtilis co-expressing ADH and ALDH was successfully constructed. It decreased increase of blood alcohol content in alcohol-treated mice. It restored the microbial composition, in particular pathogenic H. hepaticus . It could act as a novel candidate probiotic to alleviate acute alcoholic liver injury. Abstract: Alcohol consumption increases the risk of liver disease. Here, we investigated the effects of Bacillus subtilis co-expressing alcohol dehydrogenase (ADH) and acetaldehyde dehydrogenase (ALDH), key enzymes in ethanol degradation, on acute alcohol-induced liver injury. Recombinant B. subtilis significantly alleviated alcohol-induced increase in the liver index, blood alcohol content, and serum alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase activities. Furthermore, administration of ADH/ALDH-expressing B. subtilis inhibited lipid peroxidation and oxidative stress in the liver of alcohol-treated mice as evidenced by significant reduction of malondialdehyde and induction of total antioxidant capacity and glutathione and superoxide dismutase levels. Caecal microbiota diversity analysis indicated that administration of recombinant B. subtilis reversed alcohol-induced decrease in Firmicutes and increase in Proteobacteria, in particular pathogenic Helicobacter hepaticus, restoring the microbial composition in alcohol-treated mice. In conclusion, recombinant B. subtilis expressing ADH and ALDH could act as a novel candidate probiotic for prevention of alcohol-induced acute liver injury.